ГЕОЛОГИЧЕСКИЕ УСЛОВИЯ НЕФТЕГАЗОНОСНОСТИ ЧЕХЛА СИБИРСКОЙ ПЛАТФОРМЫ - Старосельцев В.С. (My University, 2002)
Кратко охарактеризованы основные геологические особенности чехла Сибирской платформы, влияющие на его нефтегазоносность. Основное внимание уделено его стратиграфическому диапазону и толщине в пределах основных структур, трапповому магматизму, неотектонике.

The basic geological features of a cover of the Siberian platform, influencing on its oil and gas content, are briefly characterized. The basic attention is given to stratigraphic range and thickness of cover within the limits of basic structures, trap magmatism, neotectonics.
Keywords: 553.98(571.5)